Haptics : Science, Technology, Applications : 12th International Conference, EuroHaptics 2020, Leiden, The Netherlands, September 6–9, 2020, Proceedings /: Science, Technology, Applications : 12th International Conference, EuroHaptics 2020, Leiden, The Netherlands, September 6–9, 2020, Proceedings. (2020) - Unknown
No abstract available